Regulation of Lipid Metabolism by Lamin in Mutation-Related Diseases - Yue Peng; Qianyu Tang; Fan Xiao; Nian Fu; Nian Fu (Frontiers Media S.A., 2022)
Nuclear lamins, known as type 5 intermediate fibers, are composed of lamin A, lamin C, lamin B1, and lamin B2, which are encoded by LMNA and LMNB genes, respectively. Importantly, mutations in nuclear lamins not only participate in lipid disorders but also in the human diseases, such as lipodystrophy, metabolic-associated fatty liver disease, and dilated cardiomyopathy. Among those diseases, the mechanism of lamin has been widely discussed. Thereby, this review mainly focuses on the regulatory mechanism of the mutations in the lamin gene in lipid alterations and the human diseases. Considering the protean actions, targeting nuclear lamins may be a potent therapeutic avenue for lipid metabolic disorders and human diseases in the future.